Estudantes surdos no PROEJA : o que nos contam as narrativas sobre os seus percursos? - Bregonci, Aline de Menezes (2012)
The present study, Deaf Students in Proeja: what do the narratives tell us about their journeys? , discusses the paths taken by young or adult deaf students at IFES, the Federal Institute of Education, Science and Technology of the State of Espírito Santo, which occurred within the Proeja, the National Program for the Integration of Vocational with Basic Education in the Modality of Youth and Adult Education. This paper aimed to trace these journeys through the narratives and from them look for answering some questions. The interest in this subject came up due to recent movements in which the deaf community has been engaged in order to establish a national policy that ensures access and permanence of the deaf students in the school. This study also aims to highlight the educational places where the deaf have been occupying and how this training process has been for the labor market. As the specific aims of this paper we highlighted the following topic: a) the realization of a historical review of the Deaf Education; b) the discussion of legal issues related to the right of deaf education; c) the identification of the places in which occurred the dialogue among the Youth and Adult Education, the Education of the Deaf and the Technological and Professional Education; d) to point out some possible alternatives for the development of the deaf and their integration into the labor market. We used the narratives as the methodology of this study in order to involve the participants in the process of including the deaf people at IFES. First, we traced the history of the Deaf Education as a way to collect data concerning what the bibliographic sources tell us about this process. Then, we present a legal discussion that intends to find, within the law, subsidies to ensure that deaf have access to an education that considers the labor market. Finally, we traced the paths of deaf students in the Federal Institute of Espírito Santo, highlighting the movements that emerged within the institute due to the inclusion of these students. We also questioned the practices in this process and we reflected over the events that occurred along this walk.There were many events, happenings, real movements that deserve our reflection because the experience lived there has a lot to contribute, mainly on ways to ensure that other deaf students have access not only at IFES but in every school. And also, we point another working alternative with deaf people, concerning to the EJA and the training to the world that is the work of EJA Garoto, a space where we can talk with other deaf people who want professional training, to know what are their life projects and career prospects.